Effects of L-Carnitine Theraphy On Methabolic and Biochemical Changes Caused By Propofol Infusion in Rabbits Undergoing Mechanical Ventilation - Savaş Yılbaş; Banu Ayhan; Burcu Akbay; Bayram Karataş; Seda B.Akıncı; Fatma Sarıcaoğlu; Ülkü Aypar (Galenos Yayinevi, 2011)
Objective: Increased lipid mass in the body secondary to long term and high doses of propofol infusion may cause carnitine deficiency. In this study; we aimed to investigate the effects of carnitine, given for treatment purposes and have not been analyzed before, during high doses of propofol infusion in rabbits. Materials and Methods: Following ethical committee approval; 2500-3500 grams weight, 3-4 months-old, healthy, male, white 20 New Zealand rabbits were included in the study. The rabbits were premedicated with xsilazine and atropine. After the preparation period including tracheostomy, monitorization, catheterization of the ear arteries and veins and urinary vesical; basal blood samples for biochemical and metabolic parameters included in the study were taken and rabbits were divided into 4 groups, 5 rabbits in each,randomly (Group P, Group PC, Group S, Group SC). For sedation 20 mg/kg/h propofol infusion was given to Group P, 20 mg/kg/h propofol and 100 mg/kg L-carnitine infusions were given simultaneously to Group PC, sevoflurane for sedation was given to Group S, sevoflurane and L-carnitine infusion were given simultaneously to Group SC. Their sedation levels were evaluated every 30 minutes and their vital signs were reported every 15 minutes. Every 2 hours arterial blood gases analysis and every 12 hours electrolytes and metabolic parameters were repeated. Euthanasia with high doses (60 mg/kg) of ketamin is performed for rabbits that were alive at the end of 24 hours. Results: All groups were similar in weight, vital parameters, all parameters searched in arterial blood gases, life time, liver enzymes, lactate dehydrogenase, serum electrolytes, creatine kinase and renal function tests (p>0.05). However; amylase levels before death or euthanasia were lower in Group PC compared to other groups;myoglobin and CK-MB levels in Group P were higher compared to other groups; cholesterol levels at 12th hour, before death or euthanasia were higher in Group P and Group PC compared to other groups; low density lipoprotein levels at 12th hour were higher in Group S and Group SC compared to other groups (p<0.05). Conclusion: In the light of the results of our study; we think that further research investigating carnitine and its metabolites during increased lipid mass in the body secondary to long term and high doses of propofol infusion or its suspicion in humans and carnitine replacement in the case of carnitine deficiency. (Journal of the Turkish Society Intensive Care 2011; 9:38-47)